Mitochondrial morphology and ultrastructure in skeletal muscle - Picard, Martin (Henry Stewart Talks, 2018)
Mitochondrial morphology transitions, Endosymbiosis, Scanning & transmission electron microscopy of mitochondria, Intermyofibrillar and subsarcolemmal mitochondria, Metabolism & regulation of mitochondrial dynamics, Transmitochondrial cristae coordination, Inter-mitochondrial junctions, Mitochondrial ultrastructure in mitochondrial disease, Reconstructions and quantitative morphometry, Multivariate analysis, Mitochondrial nanotunnels